Highly Sensitive Electrochemical Determination of Phosphoprotein Based on Novel 3D-CuFC-C Nano-material - Jianping GUO; Jingwen WANG; Lele YUE; Mengmeng REN (Shipin gongye ke-ji)
In this study, a sensitive electrochemical sensor for trace phosphoproteins monitoring in foods were developed. The sensor (NH2-TiO2/CuFC-C/GCE (TIECS)) was composed of recognition element aminated titanium dioxide (NH2-TiO2) and three-dimensional (3D) nanocomposite (CuFC-C), which were prepared through electropolymerizing reducing carboxylated graphene oxide (rGO-COOH) and CuNPs, as well as nano-layer NH2-TiO2 on glassy carbon electrode (GCE) at room temperature. The optimal detection conditions were as follows: The electro-polymerization cycles of rGO-COOH were 5, the electrodeposition time of CuNPs was 400 s, the electro-polymerization cycles of NH2-TiO2 were 9, the buffer solution was at pH6.5, β-casein underwent equilibrium adsorption for 30 minutes. Additionally, the detection voltage was maintained within the range of 0.2~1.0 V. Based on the above optimal conditions, a large linear detection range from 10−14~100 mg/mL with a low detection limit (3.82×10−17 mg/mL) and with correlation coefficients (R2) of 0.9946 was obtained via the TIECS system. The sensor exhibited remarkable selectivity against common interfering proteins. Moreover, it demonstrated excellent reproducibility and long-term stability, with relative standard deviation (RSD) of 2.42% and 1.04% respectively. Compared with the traditional laser desorption ionization−time-of-ﬂight mass-spectrometry (MALDI-TOF MS), this prepared sensor had advantages such as lower cost and greater ease of operation. It was well-suited for the rapid detection of trace phosphoproteins in food. The successful application of the TIECS sensing platform to actual samples provides a potential platform for evaluating the nutritional properties of various foods and developing the functional foods.